New antelope fossils from Awash, Ethiopia, and phylogenetic analysis of Hippotragini (Bovidae, Mammalia) - Vrba, Elizabeth S; Gatesy, John (Bernard Price Institute for Palaeontological Research, 1994)
New hippotragine antelope fossils from the Middle Awash, Ethiopia, include a new species Praedamalis howelli from Maka, an early species of Oryx from Matabaietu, and Hippotragus gigas from Gamedah. Our comparisons of these fossils with all other known fossil and Recent Hippotragini includes a cladistic analysis. The results suggest that the two major lineages in the monophyletic Hippotragini are Hippotragus including taxa from the Siwaliks previously ascribed to Sivatragus, and a Praedamalis - Oryx sister-group. Some evolutionary and biogeographic implications of the new fossils from the Middle A wash deposits are discussed.
Keywords: Hippotragini; Awash; Praedamalis